Indonesia’s Strategic Rationale for Championing the ASEAN Gender Mainstreaming Strategic Framework - Ilham Dary Athallah; Hayara Khairia; Tsabita Husna (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2025)
AbstractIndonesia's vigorous support of the ASEAN Gender Mainstreaming Strategic Framework (AGMSF) presents a compelling paradox. Despite possessing a comprehensive domestic legal architecture for gender equality, its championing of a regional framework appears redundant. This article argues that the apparent contradiction reflects a dual-track strategy in which regional norm-building is used to reinforce domestic governance while enhancing Indonesia’s standing in ASEAN. It examines Indonesia’s framing of the AGMSF, the factors shaping the translation of regional commitments into national practice, and how global gender norms are articulated alongside locally grounded ethical narratives. The article adopts a qualitative descriptive-analytical design grounded in constructivist International Relations. Data come from analysis of the AGMSF, Indonesian and ASEAN policy documents and official statements, and relevant scholarly and policy literature. Qualitative content analysis, supported by selective discourse analysis, is used to trace dominant themes and justifications. Findings show that Indonesia positions itself as a norm entrepreneur and presents the AGMSF as a non-coercive, capacity-building vehicle for localizing global gender equality principles to fit the ASEAN Way. It is also framed as an external lever for peer learning and reputational incentives to address persistent implementation gaps at home. The article concludes that the AGMSF is a strategic supplement rather than a redundant policy layer. It contributes to limited scholarship on ASEAN gender governance by linking norm entrepreneurship, regional institutionalism, and value negotiation. The findings imply that regionally resonant frameworks can strengthen domestic implementation and call for future comparative and field-based research across member states.